دور القروض البنكية في سد العجز التمويلي للمؤسسات الصغيرة والمتوسطة الصناعية دراسة مجموعة من المؤسسات الصناعية لولاية سطيف - بوعظم, فايزة; معيزة, مسعود أمير (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى إبراز دور القروض المصرفية في سد العجز التمويلي للمؤسسات الصناعية دراسة مجموعة من المؤسسات الصناعية لولاية سطيف. حيث تم الحصول الميزانيات وجدول حساب النتائج الخاصة بالمؤسسات الصناعية بعد التوجه إلى المركز الوطني للسجل التجاري. وقد تم في هذه الدراسة الاعتماد على أسلوب بيانات البانل لاختبار العلاقة بين المتغير التابع والمتمثل في نسبة الاقتراض والمتغير المستقل وهو مؤشر القدرة على التسديد. وأظهرت النتائج وجود علاقة ذات دلالة إحصائية بين نسبة القروض المالية ومؤشر القدرة على التسديد. This study aims to highlight the role of bank loans in bridging the financing deficit for industrial establishments, studying a group of industrial establishments for the state of Setif. The budgets and results calculation table for the industrial establishments were obtained after going to the National Center for the Commercial Registry. In this study, we relied on the panel data method to test the relationship between the dependent variable represented in the percentage of borrowing and the independent variable, which is an indicator of ability to repay. The results showed a statistically significant relationship between the percentage of financial loans and the ability to repay index
The role of bank loans in filling the financing deficit of industrial small and medium enterprises Study of a group of industrial enterprises of the state of Setif
مقال
Keywords: القروض البنكية ; نسبة الاقتراض ; المؤ ص م ; بيانات البانل